Behind the scenes of the beauty contest: Window dressing and the G-SIB framework - Markus Behn; Giacomo Mangiante; Laura Parisi; Michael Wedow (European Central Bank (ECB), 2019)
This paper illustrates that systemically important banks reduce a range of activities at year- end, leading to lower additional capital requirements in the form of G-SIB buffers. The effects are stronger for banks with higher incentives to reduce the indicators, and for banks with balance sheet structures that can more easily be adjusted. The observed reduction in activity may imply an overall underestimation of banks' systemic importance as well as a distortion in their relative ranking, with implications for banks' ability to absorb losses. Moreover, a reduction in the provision of certain services at year-end may adversely affect overall market functioning.
Keywords: G20; G21; G28; 330; bank regulation; window dressing; systemically important banks